Reliability and statistics in transportation and communication : selected papers from the 18th International Conference on Reliability and Statistics in Transportation and Communication, RelStat'18, 17-20 October, 2018, Riga, Latvia /: selected papers from the 18th International Conference on Reliability and Statistics in Transportation and Communication, RelStat'18, 17-20 October, 2018, Riga, Latvia. ([2018]) - Unknown
No abstract available